Rational choice theory and demand for petty corruption - Juraev, Javlon (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
This article studies corruption as a rational choice phenomenon. Unlike the widespread game-theory approach to explaining corrupt behaviour, this article attempts to describe corruption as continuous utility-maximizing problem. It comes up with a demand for corruption function, which shows how the readiness of a rational person to accept corrupt income depends on several factors such as official wage rate, severity of punishment, awareness of those penalties, probability of being detected and probability of being prosecuted.